PROFESIONALISME GURU MEMBANGUN KARAKTER PESERTA DIDIK - Ahmad Ahmad; Nurmaya Medopa (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2020)
The purpose of writing this article adds insight into the professionalism of Islamic religious education teachers building the character of students. Form the values ​​and characters of students that are useful. This article uses the literature study method with data collection techniques utilizing sources / materials from appropriate books and journals. This article seeks to outline the professionalism of Islamic religious education teachers building student character based on the writer's argument. Islamic religious education teachers have an important task in building students' character through a learning process that is sourced from the material taught by the Koran and Hadith as a guide to life, taught fiqh as legal signs in worship, teaches the history of Islam as an example of life, and teaches morals as a guide for human behavior whether in the category of good or bad. Therefore, Islamic religious education teachers are required to be professional in shaping the values ​​and character of students so that the personality of students is reflected in their behavior and mindset. Another thing to note is the success of learning the values ​​and character of students at school, one of which is also determined by the application of appropriate learning methods